Understanding the multi-sign communication system: A study on Peking Opera stage translation - Zhang, Jiadong; Zou, Deyan (Frontiers in Communication, 2023)
Peking Opera is an artist-centered art rather than director-centered art, and its true significance lies in its stage performance. However, the realization of the meaning of the "Performance Text" is the result of the joint action of different sign systems. Therefore, translators engaged in the stage translation of Peking Opera must understand the meaning and operation mechanism of this multi-sign system. From the perspective of theatre semiotics, this paper deconstructs the Peking Opera sign system and divide them into several subsystems, describes in detail the characteristics of each secondary system, especially their semiotization process, their manners of meaning transmission, the rules of interaction among them, and finally presents the meaning generation and communication mechanism of this "Performance Text".On this basis, the paper clarifies the main tasks and challenges faced by translators engaged in Peking Opera stage translation, is they should not only translate the language, but also need to find time and space to realize the transformation of the meaning of the non-verbal sign system. Meanwhile, this paper also pointed out that translators are faced with the challenges of the lack of Peking Opera professional knowledge and the lack of deconstruction ability of the multi-sign system